EP357/#634 Country of birth influences survival outcomes in caribbean black women with endometrial cancer. (4th December 2022) - Bowe, Saida; Sanchez-Covarrubias, Alex; Butler, Raleigh; Halliday, Darron; Pinto, Andre; Pinheiro, Paulo; George, Sophia; Schlumbrecht, Matthew
Abstract : Objectives: Prior studies have demonstrated survival differences between Black women with endometrial cancer (EC) born in the US (USB) and the Caribbean. Haitian-born (HB) and Jamaican-born (JB) women represent the largest proportion of Caribbean immigrants to the US, but these populations have not been specifically studied. Our objective was to determine if country of birth influences overall survival (OS) outcomes in Black women with EC. Methods: Using the Florida Cancer Data System (FCDS), women with EC diagnosed from 1981–2016 were identified. Demographic and clinical information were abstracted. Women who self-identified as Black and born in the US, Jamaica, or Haiti were included. Statistical analyses were performed using chi-square, Cox proportional hazards models, and the Kaplan-Meier methods with significance set at p<0.05. Results: 3434 women met inclusion criteria. Compared to USB, JB and HB had more high-grade histologies, more advanced disease, were uninsured or government-insured, and received more chemotherapy (all p<0.05) ( table 1 ). In multivariate analyses, age (HR 1.02, p=0.008), distant disease (HR 2.32, p<0.001), high-grade histology (HR 2.15, p<0.001), surgery (HR 0.23, p<0.001), and chemotherapy (HR 0.67, p=0.01) were independently associated with OS. In addition, relative to HB women, USB (HR 0.59, p=0.004), and JB (HR 0.54, p=0.026) had improved OS. Among patients with serous EC, HB women had markedly worse median OS (18.5 months) compared to USB (32.2 months) and JB (41 months) (p=0.027) ( figure 1 ). Conclusions: Country of birth affects EC survival, with Haitian women demonstrating worse outcomes. Understanding the biologic and social etiologies of these findings is necessary.